Pengaruh Green Human Resource Management Terhadap Pro –Environmental Behavior Dimediasi oleh Green Knowledge Sharing Dan Self-Efficacy pada Karyawan Hotel Bintang 3 di Jakarta Barat - Anggita Agustia; Wiwik Robiatul Adawiyah; Netania Emilisa; Tiara Puspa (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the influence green human resource management on pro-environmental behavior, mediated by green knowledge sharing and self-efficacy. The study was conducted using a quantitative approach with a survey method by collecting samples from employees of three-star hotels in West Jakarta. The research design employed hypothesis testing. Data were collected using a cross-sectional approach. The data were primary in nature and were obtained by distributing questionnaires via google forms, which were completed by 150 employees of three-star hotels in West Jakarta Secondary data were obtained from sources other than the research respondents and were collected through a literature review. The data analysis techniques included instrument testing, such as validity and reliability tests, structural equation modeling (SEM), descriptive statistical analysis using SPSS and AMOS software. The results indicate that green human resource management has a positive effect on green knowledge sharing and self-efficacy. Furthermore, green knowledge sharing and self-efficacy has a positive effect on pro-environmental behavior In addition, green knowledge sharing mediates the relationship between green human resource management and pro-environmental behavior, and self-efficacy also mediates the effect of green human resource management on pro-environmental behavior.